Bitcoin in Indonesia: Hedging or Investment Instrument? - Wardoyo, William; Nuryakin, Chaikal; Hambali, Sean (Jurnal Ekonomi Indonesia, 2020)
Uncertainties might compel many investors to hedge by buying globally traded assets, such as Bitcoin, which has also been used as a means of payment in several countries. Bitcoin does not originate from any centralized authority and cannot entirely be controlled; therefore, Bitcoin usage might potentially pose issues to the monetary authorities within a country. This paper analyzes the effect of both global and domestic uncertainty on Bitcoin's demand in Indonesia. Our result suggests that Bitcoin is used for hedging against uncertainties. The monetary policy implications of our results are also discussed.